Prediction of molten pool temperature in laser solid forming based on PSO-LSTM - Wang, Junhua; Xu, Junfei; Lu, Yan; Xie, Tancheng; Peng, Jianjun; Yang, Fang; Ma, Xiqiang (Frontiers in Materials, 2023)
The temperature of the molten pool in Laser Solid Forming has a direct effect on the dimensional accuracy and mechanical properties of the parts. Accurate prediction of the melt pool temperature is important to ensure the stability of the melt pool temperature and to improve the forming accuracy and quality of the part. In order to accurately predict the melt pool temperature, this study proposes a melt pool temperature prediction method based on particle swarm optimization (PSO) optimised long short-term memory neural network (LSTM). Using IR camera to obtain melt pool temperature data and establish LSTM melt pool temperature prediction model based on experimental data. Optimization of the initial learning rate and the number of hidden layer units of the LSTM model using the PSO algorithm to build a PSO-LSTM model for prediction of melt pool temperature. The results show that the PSO-LSTM prediction model outperforms the LSTM and Ridge Regression models in all evaluation indicators and can achieve accurate prediction of melt pool temperature.